Can digital tools be used for improving immunization programmes? - Alberto Eugenio Tozzi; Francesco eGesualdo; Angelo eD'Ambrosio; Elisabetta ePandolfi; Eleonora eAgricola; Pier Luigi eLopalco (Frontiers in Public Health, 2016)
In order to successfully control and eliminate vaccine-preventable infectious diseases, an appropriate vaccine coverage has to be achieved and maintained. This task requires a high level of effort, as it may be compromised by a number of barriers. Public health agencies have issued specific recommendations to address these barriers and therefore improve immunization programmes. In the present review, we characterize issues and challenges of immunization programmes for which digital tools are a potential solution. In particular, we explore previously published research on the use of digital tools in the following vaccine-related areas: immunization registries, dose tracking, and decision support systems; vaccine preventable diseases surveillance; surveillance of adverse events following immunizations; vaccine confidence monitoring; delivery of information on vaccines to the public. Subsequently, we analyze the limits of the use of digital tools in such contexts and envision future possibilities and challenges.